Juridical Review of Traffic Violations Committed by School Children (Case Study of High Schools in Surakarta City) - Candra Nur Alim; Moh Indra Bangsawan (Universitas Muhammadiyah Surakarta, 2023)
This study aims to conduct a juridical review of traffic offenses committed by school children, with a focus on high school students in Surakarta City. Traffic violations committed by school children can have serious consequences, such as traffic accidents and physical injuries, as well as have a negative impact on legal awareness and compliance with traffic regulations among the younger generation. The research method used is normative legal research with a case study approach. The data obtained was collected through literature research, analysis of laws and regulations, and field observations related to traffic violations committed by high school students in Surakarta City. The results of this study provide a clear picture of the types of offenses often committed by high school students, as well as the legal consequences they may face. The research findings show that traffic violations committed by schoolchildren include using motorcycles without helmets, going against the flow of traffic, violating traffic signs, and using cell phones while driving. The possible legal consequences faced by high school students include prosecution by police officers, payment of fines, and revocation of driving licenses.